GUGATAN ACTIO PAULIANA UNTUK MENYELAMATKAN HARTA PAILIT DALAM KEPAILITAN - Ramli Siregar; Windha Windha (Universitas Sumatera Utara, 2014)
Each economic organization in any form or scale always requires the sufficient fund to enable the activities and development can be realized based on its planning. Actio Pauliana is facility provided by regulation to each creditor to submit cancelation of not required action that implemented in which the action cause the loss to the creditor in management of bankruptcy properties. The problem in this research is management of action pauliana according to Act No. 37 of 2004 concerning to the Bankruptcy and Postponement of liability for debt payment. The authority of commerce court in action pauliana claim is to save the bankrupt property in bankruptcy. The approach method applied in this research is normative juridical method, i.e. law research by focus to the library material or document that known as secondary data in addition to primary, secondary and tertiary law material. Based on the results of research indicates that Act No. 37 of 2004 regulate. The action pauliana from Article 30, 41 up to 50 that more comprehensive than the provision or term in Civil Code (KUHPerdata) or in previous Bankruptcy Regulation (S.1905-217 in connection with S. 1906-348). Article 41 of Act No. 37 of 2004 said that for the interest of the bankrupt properties, it can apply the cancelation on all of legal action of debtor in bankruptcy that may cause the loss to the creditor that conducted before the bankruptcy. The commerce court has authority to investigate and take judgment on action pauliana in the bankruptcy case. The Commerce Court ask the curator to assess the properties of debtor after the bankruptcy decision. The application of action pauliana is a continuation of bankruptcy decision in handle the property of bankrupt. Act of bankruptcy contain the special terms on other case from the bankrupt case that decided by the Commerce Court according to Article 300 paragraph (1) of Act No. 37 of 2004. The action pauliana claim is submitted to the Commerce Court to cancel the debtor action that cause the loss to the bankrupt properties. The commerce court ask the curator to access the bankrupt properties if debtor do any action that cause the loss to the bankrupt properties. Keywords: Actio Pauliana, Harta Pailit, Kepailitan.